Association Between RSK2 and Clinical Indexes of Primary Breast Cancer: A Meta-Analysis Based on mRNA Microarray Data - Zheng, Kun; Yao, Shuo; Yao, Wei; Li, Qianxia; Wang, Yali; Zhang, Lili; Chen, Xiuqiong; Xiong, Huihua; Yuan, Xianglin; Wang, Yihua; Zou, Yanmei; Xiong, Hua (Frontiers in Genetics, 2021)
Background: Although Ribosomal Protein S6 Kinases, 90kDa, Polypeptide 3 (RSK2, RPS6KA3) has been reported to play an important role in cancer cell proliferation, invasion and migration, including breast cancer, its clinical implication in primary breast cancer patients is not well understood. And there were not many studies to explore the relationship between RSK2 and breast cancer in clinical level. Methods: A systematic series matrix files search was undertaken using Arrayexpress and Gene Expression Omnibus (GEO) database uploaded from January 1, 2008 to November 31, 2017.Search filters was breast cancer, RNA assay and array assay. Files was eligible for inclusion met the following criteria: a) sample capacity is over 100; b) tumor sample comes from unselected patient’s primary breast tumor tissue; c) expression of RSK2 and any clinical parameters of patients were available from the files. We use median as the cutoff value to assess the association between the expression of RSK2 and the clinical indexes of breast cancer patients. Finding: The meta-analysis identified 13 series matrix files from GEO database involving 3122 samples that comes from patients’ primary breast cancer tissue or normal tissue. The expression of RSK2 in tumor tissues is lower than that in normal tissues (odds ratio [OR], 0.54; 95% credible interval [CI], 0.44 to 0.67). Patients with high expression of RSK2 showed more favorable overall survival (hazard ratio [HR],0.71; 95% CI,0.49 to 0.94), less potential of distant metastasis (OR, 0.59, 95%CI, 0.41 to 0.0.87) and lymph node infiltration (OR, 0.81, 95%CI, 0.65 to 0.998). And the expression of RSK2 in luminal breast cancer is lower than that in basal breast cancer (OR, 0.25, 95% CI, 0.08 to 0.80). RSK2 overexpression correspondent with higher histological grade (OR, 1.329, 95%CI, 1.03 to 1.721). RSK2 expression is also associated with estrogen receptor (ER) and age. Conclusions: The meta-analysis provides evidence that RSK2 is a potential biomarker in breast cancer patients. The expression of RSK2 is distinctive in different intrinsic subtype of breast cancer indicate that it may play an important role in specific breast cancer. Further study is needed to uncover the mechanism of RSK2 in breast cancer.